Comparison of the neonatal outcome in mothers with gestational diabetes (GD) in two periods - Đukić, Ella (Array, 2020)
Gestational diabetes is one of the most common metabolic complications during pregnancy. Pregnant diabetic mothers, if not well regulated, are more often subject to a number of acute conditions and complications during pregnancy and childbirth. Hypoglycemia, hypocalcemia, hypertrophy, lower Apgar is often seen in children. This is a case control study. We compared mothers with GD and their infants to mothers without GD and their children both in 2015 and 2018 in order to determine whether there are any differences among them, and to compare the perinatal outcome of their infants. Examinees have been born in 2015 and 2018 (262) at KBC Osijek. The control group (262) was first neonates born after the examinees in 2015 and 2018. The results are shown in tables, with absolute and relative frequencies, and the significance of differences in the chi-square test with confidence interval at 95 %. Statistical significance will be accepted at p <0.05 level. Different acute conditions and other chronic illnesses are more common in mothers with GD. They have more complications during labor. Their infants are more often diagnosed with hypertrophy, hypoglycemia, and hypocalcemia. They also require more oxygen tratment, longer hospitalization and birth by C-section. In 2018, the number of hypoglycemic and hypocalcemic infants was twice lower, and children have been hospitalized much shorter. Better care for mothers during pregnancy and their glycemic control lead to significantly less complications in their infants and better perinatal outcome of such infants.